Determination of a clinically effective evobrutinib dose: Exposure-response analyses of a phase II relapsing multiple sclerosis study - Orestis Papasouliotis; David Mitchell; Pascal Girard; Fernando Dangond; Martin Dyroff (Wiley, 2022)
Abstract The pharmacometric analysis of the double‐blind, randomized, phase II study (NCT02975349) investigating the safety and efficacy of evobrutinib, explored exposure-response relationships and suitable dosing regimens of evobrutinib for relapsing multiple sclerosis. Population pharmacokinetic (PK)/pharmacodynamic modeling was applied to data collected in fasted patients treated with placebo or evobrutinib (25 mg once‐daily [q.d.], 75 mg q.d., or 75 mg twice‐daily [b.i.d.]) for 24 weeks, followed by a 24‐week blinded extension (placebo patients switched to 25 mg q.d.). Model‐based exposures for PK and Bruton's tyrosine kinase occupancy (BTKO) were used for exposure-response analyses (maximum 207 patients). PK, BTKO profiles, and annualized relapse rate (ARR) after 48 weeks of treatment under alternative dosing regimens were simulated. Exposure-response modeling identified a relationship between evobrutinib exposure and clinical response for total number of T1 Gd+ and new/enlarging T2 lesions at weeks 12-24, and ARR at week 48. Area under the concentration-time curve over 24 h at steady‐state (AUC0-24,SS) of 468 and ≥400 ng/ml h was associated with T1 Gd+/T2 lesion reduction and ARR improvement, respectively. These exposures were associated with steady‐state (SS) predose BTKO ≥95%. Based on PK and BTKO profile simulations, evobrutinib 75 mg b.i.d. while fasted is predicted to maintain SS predose BTKO >95% in 92% of patients. Evobrutinib 45 mg b.i.d. with food is predicted to achieve similar exposure as 75 mg b.i.d. while fasted (predose BTKO >95% in 93% of patients). Evobrutinib 45 mg b.i.d. with food is predicted to have comparable exposure and BTKO to 75 mg b.i.d. without food (phase II) and will be pharmacologically effective and appropriate for clinical use in phase III multiple sclerosis studies.